From individuals to populations : Behavioral flexibility in foraging of a wide-ranging species - Calderón Capote, Maria C. (My University, 2025)
How, when, and where animals forage determines individual survival and reproductive success. Foraging is a context-dependent behavior shaped by the interplay between the environmental and landscape conditions in which the animal lives, their individual behavior, and social interactions with others. This is particularly important for central place foragers, which travel long distances to forage and whose constant interactions at their communally-used sites can ultimately influence their foraging decisions. During my PhD, I investigated the foraging behavior of a wide-ranging bat species, the greater spear-nosed bat (Phyllostomus hastatus), at different levels of social organization, from individuals to populations. I studied a population on Isla Colón, Panama, due to the reported intraspecific variation in the species. These bats are omnivorous, feeding on temporally unpredictable resources during the dry season (e.g., the nectar and pollen of flowering balsa trees, Ochroma pyramidale) and more ubiquitous resources during the wet season (e.g., fruits and insects). They form stable groups of unrelated females known to socially forage and defend resources against other female groups during periods of temporal unpredictability, such as when balsa trees are flowering. In Panama, both female and male bats were observed commuting independently across the ocean to forage in areas over 25 km away, contrasting with previously reported shorter distances (< 10 km) and female social foraging during resource-scarce periods. Given these striking differences in social foraging behavior, the first chapter of my thesis used a longitudinal GPS-tracking dataset spanning seven years and three colonies, to investigate how P. hastatus navigate the landscape across seasons. I found that both female and male bats commuted long distances to colony-specific foraging areas, exploiting known feeding resources across years with minimal exploration. Foraging areas were shared within, but not always between, colonies. These results suggest that these bats use socially learned, colony-level foraging areas, bypassing other potentially available resources. To delve deeper into group behavior, my second chapter focused on understanding social structure and group foraging. I did this by comparing the foraging behavior of Isla Colón bats to a population in Trinidad population in relation to their resource landscapes. Using GPS tracking data from two female groups on Isla Colón, I investigated coordination in foraging behavior at different stages – departure times, return times, commutes, and foraging sites – and examined 1 how coordination was linked to their social structure. I found high intraspecific variation between the two populations. Compared to bats in Trinidad, bats on Isla Colón showed no coordination at departures or during commutes, exhibited high foraging area overlap, and had less stable female groups that were easily disturbed. These findings highlight this species' high intraspecific variation in foraging behavior in relation to the resource landscape, and the potential role of social foraging in shaping their social structure. Building on the findings of chapters 1 and 2, my third chapter tested individual consistency in foraging patterns. Following a similar approach as chapter 2, I examined within-individual and between-individual variation in departure and return times, commuting paths, and foraging areas across different seasons in two colonies. I also explored how wind and moonlight intensity – environmental factors known to influence bat foraging decisions – affected their behavior. This chapter revealed high within-individual consistency in path and site fidelity across seasons. Bats showed strong fidelity to specific paths and foraging sites, possibly adjusting their commutes to wind conditions. However, there was high individual variability in their departure times, with delays observed when there were strong wind conditions and brighter nights. These results emphasize the specialized foraging behavior of P. hastatus, highlighting the role of memory in shaping their decisions and their ability to flexibly adjust foraging timings. The remarkable flexibility of P. hastatus foraging behavior across its distribution underscores the importance to further investigate the mechanisms shaping these strategies in response to different local landscapes and environmental conditions. Furthermore, this study reinforces the need to examine behavior at multiple scales, accounting for both individual and group-level behaviors that ultimately influence population-level processes.
Keywords: Animal behavior; foraging; long-distance foraging; social foraging; Phyllostomus hastatus; foraging fidelity; neotropical bat; 570